If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = 34 + -5x Reorder the terms: 3(-2 + x) = 34 + -5x (-2 * 3 + x * 3) = 34 + -5x (-6 + 3x) = 34 + -5x Solving -6 + 3x = 34 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -6 + 3x + 5x = 34 + -5x + 5x Combine like terms: 3x + 5x = 8x -6 + 8x = 34 + -5x + 5x Combine like terms: -5x + 5x = 0 -6 + 8x = 34 + 0 -6 + 8x = 34 Add '6' to each side of the equation. -6 + 6 + 8x = 34 + 6 Combine like terms: -6 + 6 = 0 0 + 8x = 34 + 6 8x = 34 + 6 Combine like terms: 34 + 6 = 40 8x = 40 Divide each side by '8'. x = 5 Simplifying x = 5
| 7*5+ab=25+7a | | 2n-20=10 | | x^2+4x+84=0 | | 8(x+3)=2(x-36) | | 20-2n=10 | | a+b=a-b | | 8(3-y)=2+3y | | 4p+3r+7-p+2r-6= | | 5.7x=3 | | 47-6x=12x-15 | | 1/2=12x | | z=3x+8y | | (3x+8)/(8x-2)-(x+8)/(8x-2) | | 2ln(x-6)=0 | | (6y-7)/(6y+7) | | 18a+72= | | 5x+127=12x-6 | | 8m-14=3m+16 | | -56-8x+8x+24= | | 2c-5=b+23 | | 100-5h=0 | | 5(a-1)=10 | | 7y+4b=25+4*7-by | | 2n+7=5n-n | | 20-2g=6 | | 5x-3=12-52 | | 28-(-18)/-2-15(-2)(-6)/3 | | 7x+12=95+x | | 7x+12=95+3 | | 3x-1/4-5=x/2+1 | | 7y+bx=25+7x-by | | N/5+4=0 |